Differential income taxation and household asset allocation - Richard Ochmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper empirically investigates the effects of differential income taxation on households' portfolio choice and asset allocation applying a two-stage budgeting model of asset demand to German survey data. The model is structured into the discrete asset choice and the continuous asset choice, and the marginal income tax rate is simulated in a module of income taxation. Households that face relatively higher tax rates are found to have relatively greater demand for tax-privileged assets than households in the lower tax brackets. The higher the marginal tax rate the greater demand is for non-owner-occupied housing, for mortgage repayments, for building society deposits, for stocks, for insurances, and for consumer credits, whereas demand is lower for owner-occupied housing, bank deposits, and bonds.
Keywords: C35; G11; H31; 330; Household asset allocation; portfolio choice; two-stage budgeting; capital income taxation; Einkommensteuer; Steuerwirkung; Privater Haushalt; Anlageverhalten; Portfolio-Management; Deutschland